Association of Metformin Use with Vitamin B12 Deficiency in Iraqi Patients with Type II Diabetes Mellitus - Diyar F. Atabi; Ahmed H. Qasim; Saad Abdul Kareem Mohammed; Ali I. Omran Al- Saadawi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Phar. B., Al-Yarmouk University College, Department of Pharmacy